Multicentered analysis of percutaneous sclerotherapies in venous malformations of the face - Schmidt, Vanessa F.; Masthoff, Max; Goldann, Constantin; Brill, Richard; Sporns, Peter B.; Segger, Laura; Schulze-Zachau, Victor; Takes, Martin; Köhler, Michael; Deniz, Sinan; Öcal, Osman; Mansour, Nabeel; et al. (Frontiers in Medicine, 2022)
Abstract Objectives To evaluate the safety and outcome of image-guided sclerotherapy for treating venous malformations (VMs) of the face. Materials and Methods A multicenter cohort of 68 patients with VMs primarily affecting the face was retrospectively investigated. In total, 142 image-guided sclerotherapies were performed using gelified ethanol and/or polidocanol. Clinical and imaging findings were assessed to evaluate clinical response, lesion size reduction, and complication rates. Sub-analyses of complication rates depending on type and injected volume of the sclerosant as well as of pediatric versus adult patient groups were conducted. Results Mean number of procedures per patient was 2.1 (±1.7) and mean follow-up consisted of 8.7 months (±6.8 months). Clinical response (n=58) revealed a partial relief of symptoms in 70.7% (41/58), 13/58 patients (22.4%) presented symptom-free while only 4/58 patients (6.9%) reported no improvement. Post-treatment imaging (n=52) revealed an overall objective response rate of 86.5% (45/52). The total complication rate was 10.6% (15/142) including 4.2% (7/142) major complications, mostly (14/15, 93.3%) resolved by conservative means. In one case, a mild facial palsy persisted over time. The complication rate in the gelified ethanol subgroup was significantly higher compared to polidocanol and to the combination of both sclerosants (23.5% vs. 6.0% vs. 8.3%, p=0.01). No significant differences in complications between the pediatric and the adult subgroup were observed (12.1% vs. 9.2%, p=0.57). Clinical response did not correlate with lesion size reduction on magnetic resonance imaging (MRI). Conclusion Image-guided sclerotherapy is effective for treating VMs of the face. Clinical response is not necessarily associated with size reduction on imaging. Despite the complex anatomy of this location, the procedures are safe for both adults and children.